The Language of Negotiation in Management Training - Neumann, Ingrid (HERMES - Journal of Language and Communication in Business, 1993)
In this paper teaching Negotiation in a foreign language is seen as teaching 'the language of Negotiation' rather than teaching Negotiation techniques. One teaching project in a Norwegian firm is described. Method and content in the course are based on research using Negotiation data and on an 'on-line' needs analysis. Two teaching units are focused on: questions and 'meta-labels'.